Oportunidades de capacitação de profissionais para atender as exigências da Lei Geral de Proteção de Dados - Monteiro, Cesar Augusto (2020)
The purpose of this paper is to present the identification and use of a business opportunity that arose with the implementation of the General Regulation on Data Protection in the European Union and the General Data Protection Law (LGPD), equivalent legislation in Brazil in 2018: the provision of Data Protection Officer (DPO) training and certification, specialized professionals and those responsible for complying with the requirements of this legislation in corporations. Through a technical report, the entrepreneur's decision-making process is presented, from diagnosis, identification of alternatives, followed by the business model, with open training and corporate classes. The work finally analyzes the entrepreneur's decision-making process, which is supported by the effectuation theory, when presenting the bases for his behavior, after the solution has been implemented, the preliminary results indicate that the strategy was correct, although some adjustments to the model will need to be made. to suit some new identified demands.